The Houses of the Princesses Joanna, Isabel, and Violant (1375-1392): Formation, Composition, and Characteristics of Minor Curial Areas - Stefano Maria Cingolani (Royal Studies Journal, 2023)
The purpose of this study is to examine for the first time the formation, composition, and functioning of the houses of three unmarried princesses (infantas) of late fourteenth-century Spain; to consider the purposes of the houses and situate them within the complex galaxy of households belonging to kings and princes of the time; and, finally, to propose some subjects worthy of further investigation.